THE INFLUENCE OF ONLINE CUSTOMER REVIEWS, ONLINE CUSTOMER RATINGS, AND STAR SELLERS ON CONSUMER TRUST IN THE SHOPEE MARKETPLACE IN LHOKSEUMAWE CITY - Monica Juliani Sagala; Ikramuddin; Adnan; Mariyudi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the Influence of Online Customer Reviews, Online Customer Ratings, and Star Sellers on Consumer Trust in the Shopee Marketplace in Lhokseumawe City. This study uses primary data obtained by distributing questionnaires to 133 respondents selected using non-probability and purposive sampling methods. The population in this study were consumers who had made purchases on the Shopee Marketplace. This study uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The results of this study partially indicate that online customer reviews have a positive and significant effect on consumer trust in the Shopee Marketplace in Lhokseumawe City, online customer ratings have a positive and significant impact on consumer trust in the Shopee Marketplace in Lhokseumawe City, and star sellers have a positive and significant effect on consumer trust in the Shopee Marketplace in Lhokseumawe City. Simultaneously, online customer reviews, online customer ratings, and star sellers have a significant effect on consumer trust in the Shopee Marketplace in Lhokseumawe City.